2013
DOI: 10.1002/ejic.201301031
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Magnetic Exchange Pathways in Heterotrinuclear Manganese(III) Schiff Base Complexes Involving Tetrathiocyanidoplatinate(II) Bridges

Abstract: The first heterotrinuclear manganese(III) Schiff base complexes involving tetrathiocyanidoplatinum(II) bridges with the general formula [{Mn III (L4)(Solv)} 2 {μ-Pt II (SCN) 4 }] {for which L4 2is a tetradentate dianionic Schiff base ligand; (1c), and Solv = CH 3 OH (1a, 1b) or H 2 O (1c)} were synthesized and characterized. The two terminal [Mn(L4)(Solv)] + subunits are covalently bridged by [Pt(SCN) 4 ] 2moieties in a trans arrangement. The coordinated solvent (Solv) ligands form intermolecular hydrogen bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…However, the D-parameter does not simply correlate with geometric deformation of the coordination chromophore (Σ), which can be explained by the complexity and variedness of the donor atoms. Conversely, there are some remarks concerning the isotropic exchange which must be taken into account: our previous results 20 predicted weaker exchange interactions within the supramolecular dimer [M(L4)(Solv)] + ⋯[M(L4)(Solv)] + when Solv = CH 3 OH and stronger ones when Solv = H 2 O. As can be seen from Table 3, this prediction holds true; the compounds containing [M(L4)(CH 3 OH)] + fragments possess weaker exchange interactions with J values ranging from −0.3 to −0.6 cm −1 , while the compounds containing [M(L4)(H 2 O)] + fragments have lower J values ranging from −0.7 to −1.3 cm −1 (when not including most probably overestimated J values, due to the ZFS term being omitted in the magnetic data analysis, for details see Table 3).…”
Section: Trinuclear [{Fe(l4)(h 2 O)} 2 {μ-Fe(cn) 5 (No)}]•xch 3 Oh Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the D-parameter does not simply correlate with geometric deformation of the coordination chromophore (Σ), which can be explained by the complexity and variedness of the donor atoms. Conversely, there are some remarks concerning the isotropic exchange which must be taken into account: our previous results 20 predicted weaker exchange interactions within the supramolecular dimer [M(L4)(Solv)] + ⋯[M(L4)(Solv)] + when Solv = CH 3 OH and stronger ones when Solv = H 2 O. As can be seen from Table 3, this prediction holds true; the compounds containing [M(L4)(CH 3 OH)] + fragments possess weaker exchange interactions with J values ranging from −0.3 to −0.6 cm −1 , while the compounds containing [M(L4)(H 2 O)] + fragments have lower J values ranging from −0.7 to −1.3 cm −1 (when not including most probably overestimated J values, due to the ZFS term being omitted in the magnetic data analysis, for details see Table 3).…”
Section: Trinuclear [{Fe(l4)(h 2 O)} 2 {μ-Fe(cn) 5 (No)}]•xch 3 Oh Co...mentioning
confidence: 99%
“…In our previous work we have reported coordination compounds built from various [Mn III (L4)] + moieties bridged by [Pt(SCN) 4 ] 2− or [Pt(SCN) 6 ] 2− complex anions. 20,21 Almost all of the prepared compounds were trinuclear with the general formula [{Mn(L4)(Solv)} 2 {μ-Pt (SCN) x }], where x = 4 or 6, and they thus belong to group (A). For those compounds it was shown that the exchange interactions mediated by the diamagnetic bridging anion are negligible and it was proven that the dominant magnetic exchange pathway occurs via non-covalent interactions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Such reactions lead to preparations of compounds related to Prussian blue [6,7,8,9,10,11]. Previously, we reported on crystal structures and magnetic properties of polymeric and polynuclear compounds involving the [Mn(L4)] + moieties which were bridged by [Fe(CN) 5 (NO)] 2− , [Pt(SCN) 4 ] 2− and [Pt(SCN) 6 ] 2 complex anions [12,13,14]. This work represents a continuation of our ongoing study of platinum cyanido/thiocyanido bridged heterometallic compounds and reports on two new Mn III ···Pt II compounds involving the [Pt(CN) 4 ] 2− bridges: i.e., [{Mn(L4A)} 2 { µ 4 -Pt(CN) 4 }] n ( 2a ) and [{Mn(L4B)} 2 { µ -Pt(CN) 4 }] ( 2b ), where H 2 L4B = N , N ’-benzene-bis(4-aminodiethylenesalicylideneiminate) (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%